Frying quality of virgin coconut oil as affected by zea mays extract - Marina, A.M.; Wan Rosli, W.I.; Neoh, S.L. (Universiti Kebangsaan Malaysia, 2014)
The effect of corn silk or Zea mays extract on the physicochemical changes of virgin coconut oil was studied during three consecutive days of deep frying. There were three types of oil blend systems used: virgin coconut oil without antioxidant as control system; virgin coconut oil with butylated hydroxytoluene (BHT) as synthetic antioxidant and virgin coconut oil with Zea mays extract as natural antioxidant. The oil quality was assessed by measuring the colour, viscosity, peroxide, p-anisidine, free fatty acids, totox and iodine value. The results show that Zea mays extract delayed the oil deterioration. The Zea mays extract significantly (p<0.05) lowered the rate of oxidation in virgin coconut oil compared to control oil and was comparable to BHT. Zea mays extract did not change the sensory profiles of French fries which was shown by insignificant difference (p<0.05) between Zea mays and control fries for all sensory attributes (colour, taste, aroma, crispiness, oiliness and overall quality). In general, the Zea may extract was capable of extending the stability and quality of virgin coconut oil and therefore has potential as new source of natural antioxidant for use in deep frying.